THE EFFECT OF TAX AVOIDANCE AND OWNERSHIP STRUCTURE ON COST OF DEBT - Alfiyan Abdussa'id (2021)
This research aims to determine the effect of tax avoidance and ownership structure which is divided into institutional, family, and managerial ownership on cost of debt of all non-financial companies listed in Indonesia Stock Exchange in the period 2015 - 2019. The type of this research is quantitative research that uses secondary data based on annual report. Sample from this research consisted of 75 companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linier regression, and partial hypotesis testing (T test). Based on the result of data analysis, it can be concluded that (1) tax avoidance has a negative significant effect on cost of debt, (2) institutional ownership has no effect on cost of debt, (3) family ownership has no effect on cost of debt (4) managerial ownership has no effect on cost of debt cost of debt and control variable, namely (5) company size has no effect on cost of debt